The Energy Charter Treaty, a chronicle of an announced withdrawal? - Goyanes, Rocio (2025)
The origin of the ECT dates to the end of the Cold War, where the historical context provided an opportunity for cooperation in the energy sector between Eastern and Western European countries. However, in recent years, the Member States of the European Union have expressed strong criticisms of the ECT, finding it incompatible with the obligations assumed by the European Union in environmental treaties. This articleseeks to analyze the current landscape of ECT disputes, the criticisms that led to a process of modernizing the original ECT text, and the probable outcomes of this modernization process considering the European Union's critical stance regarding the investor-state dispute resolution system. We cannot help but wonder: are we witnessing the chronicle of a withdrawal announced by the European Union Member States?